2021
DOI: 10.36937/cebacom.2020.003.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermal Effects on Slag Cement Concrete’s Strength Properties

Abstract: The physical, chemical, and mechanical characteristics of concrete change with heat-fire. The effect of thermal load on Slag cement concrete output must be measured because of the crucial role of thermal resistance in concrete structure performance and operation. This work examines the thermal resistance of Slag cement concrete. The concrete cubes were produced and cured for 28 days and then subjected to varying temperatures range of 100°C, 150°C, 200°C, 250°C, and 300°C. Hardness and compressive strength were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The sun's radiation may also raise the road surface temperatures and the temperature but will have an even more significant effect on the asphalt pavement temperature. A numerical method based on finite-difference modeling is proposed by [30], which evaluates temperature distribution in pavements depending on changes in the thermal environment. The model anticipates temperature variations in rates and depth during freezing and thawing cycles.…”
Section: Main Factors Contributing To Temperature Variations Of Aspha...mentioning
confidence: 99%
“…The sun's radiation may also raise the road surface temperatures and the temperature but will have an even more significant effect on the asphalt pavement temperature. A numerical method based on finite-difference modeling is proposed by [30], which evaluates temperature distribution in pavements depending on changes in the thermal environment. The model anticipates temperature variations in rates and depth during freezing and thawing cycles.…”
Section: Main Factors Contributing To Temperature Variations Of Aspha...mentioning
confidence: 99%
“…These are examples of non-ferrous materials. The bulk of these materials is recyclable in some form or another [58]; [55].…”
Section: Nonferrous Metalsmentioning
confidence: 99%
“…Although recycling is widely accepted as the most effective strategy for achieving long-term sustainability, real-world implementation has proven to be challenging [21]. [55] suggested that recycling waste is more practical than reducing and reusing waste.…”
Section: Recycling Of Cdwmentioning
confidence: 99%
See 2 more Smart Citations